On the optimum geometric shapes of ZnSe-based scintillation elements - Katrunov, K.; Naydenov, S.; Ryzhikov, V.; Starzhinskiy, N.; Gal’chinetskii, L.; Gavril’uk, V.; Yanovsky, V. (Вопросы атомной науки и техники, 2004)
We have carried out Monte-Carlo calculations of the light collection coefficient τ for different shapes of ZnSebased scintillators Applying a theoretical model, it has been shown, that the light collection optimization can be
reached in scintillators with a geometry where the chaotic light collection is realized. Experimentally it was
supported that for detectors of rectangular and cylindrical types with rounded vertexes or edges, the light output
increase of up to 20% has been observed, provided the regular light beam dynamics was changed to chaotic. З використанням методу Монте-Карло проведені розрахунки коефіцієнта світлозбирання для різних
форм сцинтиляторів на основі ZnSe. Теоретично показано, що оптимізація світлозбирання досягається у
сцинтиляторах з геометрією, у якій реалізується хаотичне збирання світлових променів. Це припущення
експериментально підтверджено на прикладі детекторів прямокутного і циліндричного типу з округленими
вершинами та ребрами, для яких виявлено підвищення світлового виходу до 20 % при заміні регулярної
динаміки світлових променів на хаотичну. С использованием метода Монте-Карло проведены расчеты коэффициента светособирания для
различных форм сцинтилляторов на основе ZnSe. Теоретически показано, что оптимизация светосбора
достигается в сцинтилляторах с геометрией, для которой реализуется хаотическое собирание световых
лучей. Это предположение экспериментально подтверждено на примере детекторов прямоугольного и
цилиндрического типа со скругленными вершинами или ребрами, для которых обнаружено повышение
светового выхода до 20% при изменении регулярной динамики световых лучей на хаотическую.